The demographics of fat talk in adult women: Age, body size, and ethnicity. (August 2016) - Engeln, Renee; Salk, Rachel H
Fat talk, conversations in which women disparage the size/shape of their bodies, acts as both a reflection of and contributor to body dissatisfaction. We assessed the impact of age, body mass index, and ethnicity on fat talk in two large, online surveys of adult women. Body mass index showed a small, positive correlation with fat talk, but only for women who were not overweight. Fat talking was common across all ages. In contrast to the common belief that fat talk is limited to young, thin women, these studies demonstrate that women of many body sizes and ages engage in fat talk.